ANALYSIS OF ISLAMIC RELIGIOUS RELIGIOUS EDUCATION TEACHER'S PEDAGOGIC COMPETENCE IN CURRICULUM DEVELOPMENT - Musaitir Fahmi; Suhirman Suhirman; Al Kusaeri (Conciencia, 2022)
The objective of this research was to analyze The teachers’ Pedagogical competence in curriculum development, the obstacles faced in curriculum development, and how efforts were made to improve curriculum development at a Madrasah in Kalijaga. The Pedagogic competence of Islamic religion teachers has a critical role in implementing the curriculum. Managing Pedagogic competence, especially in curriculum development, becomes a common problem found in realizing learning objectives. This research used a descriptive qualitative method. Observation, interviews, and documentation are the data collection technique. The result of the study describes that the pedagogic competence of PAI teachers at a Madrasah, especially in developing curriculum, syllabus, and lesson plans, is good. Most PAI teachers have made learning devices such as syllabi, an annual program, a semester program, implementation of teaching and learning and teaching, and learning evaluation. Although one or two teachers still have not completed their learning devices before entering the class to teach.